The Design and Development of a Prayer Counter - Mohd Nizam Sudin (Universitas Pendidikan Indonesia (UPI), 2023)
This paper presents the systematic design process and prototype development of a prayer counter. The prayer counter is used to count the number of units of prayers or raka’at, based on the number of prostrations. The unit of prayer is determined by the accumulated number of prostration, which are two prostrations for one unit of prayer. The prayer counter receives an input signal from the input unit as it is actuated by an individual in prayer. The actuation of an input unit begins as an individual’s head touches the input unit in prostration. The input signal will be converted into an output signal and displayed with a Light Emitting Diode (LED). Users of the prayer counter can see the current unit of prayer through the display unit indicator. The LED’s lights indicate the current number of prostrations and indirectly indicate the current unit of prayer. The result of product testing, and initial evaluation of the product, shows that the prayer counter can display the number of prostrations and units of prayer precisely. It is therefore able to avoid doubt in the number of prayer units, if the individual gets distracted in prayer. In addition, the responses received from potential users, about the benefit of the product to them, was very positive. In conclusion, considering the relevant issues of the product being designed is the most important step of the design process.